2015
DOI: 10.3390/jof1010013
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Treatment for Pityriasis Versicolor

Abstract: Background: Pityriasis versicolor (PV), also known as tinea versicolor, is caused by Malassezia species. This condition is one of the most common superficial fungal infections worldwide, particularly in tropical climates. PV is difficult to cure and the chances for relapse or recurrent infections are high due to the presence of Malassezia in the normal skin flora. This review focuses on the clinical evidence supporting the efficacy of antifungal treatment for PV. Method: A systematic review of literature from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
63
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 53 publications
1
63
0
5
Order By: Relevance
“…The biological prevalence obtained through the cellophane tape method showed that there was an overestimation of the disease prevalence at the clinical Silva-Rocha et al, 2017). That could be explained by the previous use of specific treatments not reported by the patients or by the persistence of lesion discoloration even after healing (Gupta and Foley, 2015). It is therefore essential to combine mycological analysis with the relatively simple clinical diagnosis for appropriate management of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological prevalence obtained through the cellophane tape method showed that there was an overestimation of the disease prevalence at the clinical Silva-Rocha et al, 2017). That could be explained by the previous use of specific treatments not reported by the patients or by the persistence of lesion discoloration even after healing (Gupta and Foley, 2015). It is therefore essential to combine mycological analysis with the relatively simple clinical diagnosis for appropriate management of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore essential to combine mycological analysis with the relatively simple clinical diagnosis for appropriate management of the disease. A diagnosis of PV can be confirmed by microscopy using skin scrapings from theborders of lesions in a KOH mount or by obtaining samples using the cellophane tape method (Gupta and Foley, 2015), as in this study. The two techniques are similarly reliable (Hassab-El-Naby et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Among systemic antifungal, ketoconazole was once the gold standard for oral treatment. Currently, itraconazole, fluconazole, and pramiconazole are effective antifungals [6]. Patients of PV should be counselled that hyper-or hypopigmentation may persist and may take months to recover normal skin appearance despite successful treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In an individual, lesions of PV are typically of uniform color though light and dark lesions can coexist, with the darker lesions appearing in untanned areas[1]. They can occur on the trunk and extremities and are more prevalent in climates with increased humidity[1].Malassezia normally colonize the skin in humans, are highly lipophilic and appear to result in clinical disease when host and environmental factors permit, such as change in sebum production, increase in humidity, increased sweat production, as well as familial factors[1,2]. Diagnosis is confi rmed by the demonstration of budding yeast and hyphae "spaghetti and meatballs" pattern on potassium hydroxide (KOH) preparation of a scraping of a skin lesion[1].…”
mentioning
confidence: 99%
“…This was demonstrated in our patient in fi gure 3. Treatment for PV consists of topical antifungal agents, terbinafi ne and ketoconazole, or oral antifungals, fl uconazole, itraconazole, or ketoconazole, which all result in high cure rates[2]. However oral ketoconazole is no longer recommended for superfi cial dermatophyte infections by the Food and Drug Administration and has received a black box warning regarding hepatotoxicity with its use[3].…”
mentioning
confidence: 99%